Republic of Armenia : Second Review Under the Stand-By Arrangement, Requests for Augmentation of Access, Modification of Performance Criteria, and Monetary Policy Consultation Clause-Press Release; Staff Report; Staff Supplement; and Statement by the Alternate Executive Director. (IMF Staff Country Reports; Country Report, 2020)
This paper discusses Republic of Armenia's Second Review Under the Stand-By Arrangement, Requests for Augmentation of Access, Modification of Performance Criteria, and Monetary Policy Consultation Clause. Following a strong performance in 2019, the Armenian economy was hit hard by the coronavirus disease 2019 pandemic. The government has proactively responded to the crisis, adopting widespread containment measures while supporting vulnerable individuals and firms in the most affected sectors. The fiscal deficit is projected to widen considerably in 2020, reflecting the impact of the cycle on revenues and higher current spending for healthcare and economic support to vulnerable households and firms. The authorities are committed to pursuing their medium-term goal of debt sustainability once the crisis abates, and public debt is expected to decline over the medium-term in line with Armenia's fiscal rule, while maintaining space for investment and social spending. The augmentation of access under the Stand-by Arrangement will provide much needed support, allowing the authorities to mitigate the pandemic and support affected households and businesses.